Effectiveness of intralesional sodium stibogluconate for the treatment of localized cutaneous leishmaniasis at Boru Meda general hospital, Amhara, Ethiopia: Pragmatic trial. - Feleke Tilahun Zewdu; Asressie Molla Tessema; Aregash Abebayehu Zerga; Saskia van Henten; Saba Maria Lambert (Public Library of Science (PLoS), 2022)
Background Cutaneous leishmaniasis (CL) is generally caused by Leishmania aethiopica in Ethiopia, and is relatively hard to treat. Sodium stibogluconate (SSG) is the only routinely and widely available antileishmanial treatment, and can be used systemically for severe lesions and locally for smaller lesions. There is limited data on the effectiveness of intralesional (IL) SSG for localized CL in Ethiopia and therefore good data is necessary to improve our understanding of the effectiveness of the treatment. Methodology/principal findings A pragmatic (before and after Quazi experimental) study was done to assess the effectiveness of intralesional SSG among localized CL patients at Boru Meda general hospital, Northeast Ethiopia. Patients who were assigned to intralesional SSG by the treating physician were eligible for this study. Study subjects were recruited between January and August 2021. Infiltration of intralesional SSG was given weekly to a maximum of six doses. However, when a patient's lesions were already cured before getting 6 doses, treatment was not conintued, and patient were only asked to come for lesion assessment. Skin slit smears (SSS) were taken each week until they became negative. Outcomes were assessed at day 90, with patients who had 100% reepithelization (for ulcerative lesions) and/or flattening (for indurated lesions) defined as cured. Multi-level logistic regression was done to assess factors associated with cure. A total of 83 patients were enrolled, and final outcomes were available for 72 (86.75%). From these 72, 43 (59.7%, 95% confidence interval 0.44-0.69) were cured at day 90. Adverse effects were common with 69/72 patients (95.8%) reporting injection site pain. Factors associated with cure were age (OR 1.07 95% CI: 1.07-1.27), being male (OR 1.79, 95% CI: 1.10-2.25), size of the lesion (OR 0.79, 95% CI: 0.078-0.94) and skin slit smear (SSS) result +1 grading (OR 1.53, 95% CI: 1.24-1.73) and +2 grading (OR 1.51, 95% CI: 1.41-3.89) compared to the SSS grade +6. Conclusion Our findings revealed that intralesional sodium stibogluconate resulted in a cure rate of around 60%, with almost all patients experiencing injection site pain. This emphasizes the need for local treatment options which are more patient-friendly and have better cure rates.